The Historical Presidency: The Rendition of Fugitive Slaves and the Development of the Law‐and‐Order President, 1790–1860. Issue 3 (7th December 2018) - Miller, Joshua
Abstract : Presidents obtained the power to maintain law and order when they used key executive branch institutions—such as the Department of War, U.S. Attorney General's Office, and the State Department—to recover fugitive slaves. To date, there has been little discussion in political science about the development of the president's power to maintain law and order. As a result of this gap, political scientists have missed how race has contributed to the institutional development of the presidency, how nineteenth‐century presidents institutionalized the president's authority over federal law enforcement, and how the president's power to maintain law and order expands his authority over U.S. citizens via the Department of Justice. This article addresses this gap by examining the development of the law‐and‐order president from 1790 to 1860 and in the process debunks the myth that presidents were relatively weak in the nineteenth century.